2022
DOI: 10.1177/07334648221118352
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationship Between Frailty and Cognitive Impairment in Chinese Older Adults: A Prospective Study

Abstract: We aimed to examine the longitudinal association between frailty and cognitive impairment in the older Chinese population. This prospective cohort study used data from the Chinese Longitudinal Healthy Longevity Study 2011 wave. We calculated the follow-up duration as 3 years from the baseline year. Frailty was measured using the frailty index, and cognitive function was calculated by Mini-Mental State Examination Scale. Participants who were non-frailty and those with normal cognitive function were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The studies above identified how social, psychological, cognitive and environmental factors may be linked to underlying biological factors in CF. One study examined the direction of the trajectory in a longitudinal dataset (Zhao et al, 2022), determining that the accumulation of deficits associated with PF is what is driving the co-occurrence of PF and CI suggesting the predictive relationship only works in one direction. We conclude this section by reviewing evidence for biological processes underpinning CF, beyond general ageing.…”
Section: Resultsmentioning
confidence: 99%
“…The studies above identified how social, psychological, cognitive and environmental factors may be linked to underlying biological factors in CF. One study examined the direction of the trajectory in a longitudinal dataset (Zhao et al, 2022), determining that the accumulation of deficits associated with PF is what is driving the co-occurrence of PF and CI suggesting the predictive relationship only works in one direction. We conclude this section by reviewing evidence for biological processes underpinning CF, beyond general ageing.…”
Section: Resultsmentioning
confidence: 99%